The European Movement in Norway: Norway's Security and European Foreign Policy in the 198Q's. Oslo: Universitetsforlaget 1981, 81 s., Nkr. 64,00. Kontrast, nr. 4-5, 1981, tema: Europa, 80 s., Nkr. 29,00. - Martens, Hans (Politica, 1982)
-